Exploring How the Balanced Scorecard Engages and Unfolds: Articulating the Visual Power of Accounting Inscriptions - Busco, Cristiano; Quattrone, Paolo (Contemporary Accounting Research, 2015)
Abstract Research on the Balanced Scorecard ( BSC ) has questioned whether its adoption generates greater integration between financial and nonfinancial performance measures, supports strategy implementation, increases performance and improves strategic decision making. This research has also highlighted how the BSC often generates effects other than these. Building on studies that portray Performance Measurement Systems as intrinsically incomplete practices of representation, the purpose of this article is to investigate how the BSC engages users because of the organizing work that it stimulates around this incompleteness. Our findings allow us to further articulate the power of specific visual elements of the BSC , such as hierarchical trees, wheels, causal and strategy maps. The article provides material that contributes to a better understanding of how the BSC performs multiple roles within organizations beyond a simple representational functionality and unfolds continuously. It contributes to the growing literature on accounting inscriptions, that is, signs producing incomplete representations, by developing an analytical theoretical framework that defines the BSC as a rhetorical machine composed of four key features: (i) a visual performable space (i.e., a schema generating creative engagement); (ii) a method of ordering and innovation; (iii) a means of interrogation and mediation; and (iv) a motivating ritual.